Bureaucratic manoeuvres and the local politics of climate change mitigation in China and India. (20th May 2019) - Harrison, Tom; Kostka, Genia
ABSTRACT: This article explores how strategies of thinking and working politically are used by agencies within developing country governments to influence wider government agendas. It uses research on climate change mitigation in China and India to explore how government agencies seek to overcome challenges of limited capacity and competing priorities by bundling climate change together with more immediate priorities and thereby developing a coalition with an interest in achieving these objectives. The article is based on interviews conducted in China and India, as well as analysis of themes covered in the growing body of literature on the domestic politics of climate change mitigation. In both countries we found that pragmatic approaches leveraging what already exists made significant progress in putting energy efficiency on the agenda, strengthening institutional presence (in India) and delivering improvements in energy efficiency (in China). Yet, we also found that the use of these tactics had significant limitations. While there was probably no other way that the policy space given to climate change mitigation could have increased so rapidly, there are significant side effects that arise as a result of the traction gained by these initial policy approaches. While bundling raised the profile of energy efficiency, it also created perverse incentives that highlight the need to consider the long‐term effect on the interests, capacity and sustainability of informal coalitions. We highlight the need to take account of both the short‐ and long‐term effects of thinking and working politically, and the challenges of doing so when the outcomes are unpredictable and inherently difficult to assess.